Teaching the Art of Introduction: Barāʾat al-Istihlāl as a Strategy in Arabic Language Pedagogy - Menik Mahmudah; Nur Hanifansyah; Nur Aunie Batrisya (Universitas Islam Negeri Palangka Raya Raya, 2026)
In Arabic language pedagogy, students often demonstrate adequate grammatical accuracy yet struggle to produce introductions that are thematically coherent, rhetorically engaging, and contextually appropriate, reflecting a limited integration of classical rhetorical principles in modern writing instruction. This study explores the pedagogical value of Barāʾat al-Istihlāl, a classical rhetorical device traditionally used in Arabic literature to craft meaningful openings, within the context of modern Arabic language teaching. Conducted at Pondok Pesantren Darullughah Wadda’wah with 30 male Aliyah-level students, the research employed a qualitative design involving classroom observations, focus group discussions, and interviews. Findings reveal that practicing rhetorical openings not only enhanced students’ ability to write coherent and stylistically engaging introductions but also enriched their vocabulary, with learners acquiring ten to fifteen new lexical items per session. Furthermore, the practice cultivated emotional sensitivity, training students to align openings with appropriate moods and contexts such as using uplifting language for joyful occasions or solemn expressions for serious ones thereby fostering both linguistic awareness and rhetorical taste (al-Ḥass al-Lughawī wa al-Dhawq al-Balāghī). The study concludes that Barāʾat al-Istihlāl is a powerful pedagogical strategy that bridges classical rhetorical heritage with contemporary education, offering dual benefits for written composition and oral communication. Implications suggest its integration into writing classes and public speaking training to enhance students’ linguistic competence, cultural sensitivity, and persuasive ability.